PPP2R3C gene variants cause syndromic 46,XY gonadal dysgenesis and impaired spermatogenesis in humans - GÜRAN, TÜLAY; YEŞİL, GÖZDE; YEŞİL, GÖZDE; Turan, Serap; Atay, Zeynep; BOZKURTLAR, EMİNE; Aghayev, AghaRza; Gul, Sinem; TİNAY, İLKER; Aru, Basak; Arslan, Sema; Koroglu, M. Kutay; et al. (My University, 2019)
Context: Most of the knowledge on the factors involved in human sexual development stems from studies of rare cases with disorders of sex development. Here, we have described a novel 46, XY complete gonadal dysgenesis syndrome caused by homozygous variants in PPP2R3C gene. This gene encodes B - gamma regulatory subunit of the protein phosphatase 2A (PP2A), which is a serine/threonine phosphatase involved in the phospho-regulation processes of most mammalian cell types. PPP2R3C gene is most abundantly expressed in testis in humans, while its function was hitherto unknown.